2021
DOI: 10.3389/fmed.2021.645592
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Sphincter Augmentation Outcomes in Severe Gastroesophageal Reflux Disease

Abstract: Introduction: Outcomes of laparoscopic procedures for gastroesophageal reflux disease (GERD) are variable depending on surgical expertise and/or patient-related factors. Some procedures may be inadequate in patients with severe disease. Effectiveness of laparoscopic magnetic sphincter augmentation (MSA) has not been extensively tested in patients with severe disease.Methods: A prospectively collected database was analyzed to identify patients who underwent MSA at a single institution. Individuals who had previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, in the Nissen fundoplication group there was a higher rate of patients with inability to belch and vomit, along with more severe gas-bloat symptoms, whereas quality of life scores were similar in patients treated either by Linx or Toupet fundoplication [52][53][54][55][56][57][58][59]. Magnetic sphincter augmentation also proved effective in patients with severe GERD [60][61][62]. Two meta-analyses comparing Linx and fundoplication reported that the former was associated with less gas-bloat symptoms and an increased ability to vomit and belch, while PPI suspension rate, dysphagia requiring endoscopic dilatation, and GERD-HRQL were similar in the two patient groups [63,64].…”
Section: Early and Intermediate-term Outcomesmentioning
confidence: 93%
“…However, in the Nissen fundoplication group there was a higher rate of patients with inability to belch and vomit, along with more severe gas-bloat symptoms, whereas quality of life scores were similar in patients treated either by Linx or Toupet fundoplication [52][53][54][55][56][57][58][59]. Magnetic sphincter augmentation also proved effective in patients with severe GERD [60][61][62]. Two meta-analyses comparing Linx and fundoplication reported that the former was associated with less gas-bloat symptoms and an increased ability to vomit and belch, while PPI suspension rate, dysphagia requiring endoscopic dilatation, and GERD-HRQL were similar in the two patient groups [63,64].…”
Section: Early and Intermediate-term Outcomesmentioning
confidence: 93%
“…The most common indications for device removal are dysphagia and persistence of GERD symptoms, which are present at 2% and 4% of implants, respectively. 15 In absence of evidence of an endoscopic or radiologic anatomical failure, a study from our center suggests that management and decision regarding revisional antireflux surgery should be tailored to the presenting symptom. 16…”
Section: Classifying Dysfunction After Magnetic Sphincter Augmentationmentioning
confidence: 96%
“…Long-term outcomes of MSA have also been favorable [70,71]. A prospective study by Ferrari et al in 2020 followed 335 patients who underwent MSA implantation for 6 to 12 years following their procedures [70].…”
Section: Mechanical Interventionsmentioning
confidence: 99%